Aquaman. Volume 2, The Others - Johns, Geoff, 1973- (New 52., 2013)
"Six years later after a grisly murder, The Others are reunited. They know only one man could be responsible: Black Manta. Aquaman must lead the charge to stop his arch-nemesis, but will the years have fractured The Others just enough to keep them from bringing this villain to justice?"--Amazon.com.